A Devastating Case of Hepatitis C-Induced Mixed Cryoglobulinemia. (8th October 2021) - Khalid, Sameeha; Alhankawi, Dhuha; Kaur, Kamalmeet; Ali, Ali; Kazaryan, Anna; Roytman, Marina
Abstract : Hepatitis C-induced mixed cryoglobulinemia leading to rapidly progressive gangrene, necessitating amputations, is a rare presentation. We describe a case of a 55-year-old man with untreated chronic hepatitis C virus (HCV) presenting with arthralgia and palpable purpura, which rapidly progressed to life-threatening gangrene of all extremities requiring amputations in the setting of mixed cryoglobulinemia. Treatment for HCV was initiated which led to the arrest of gangrene progression and the patient's survival. Patients with HCV-induced cryoglobulinemia should be closely monitored and started on early therapy with direct-acting antiviral therapy to prevent progression of vasculitis to gangrene. Universal screening for HCV can aid in early diagnosis and treatment to prevent devastating consequences.